PENINGKATAN PEMAHAMAN ASPEK HUKUM LITERASI KEUANGAN DIGITAL BAGI SISWA SMA YAPEMRI KOTA DEPOK - Herman, KMS; Widyanto, Muhammad Laras; Ferdiles, Lucky; Nurmawati, Bernadete (LPPM Institut Pendidikan Nusantara Global, 2024)
The rapid development of technology in the digital era has brought significant changes to financial behavior in society with the emergence of digital financial systems. Financial literacy has become essential in managing personal finances, including investments, debt management, and long-term financial planning. Financial literacy enables individuals to make wise financial decisions. In the digital era, improving financial literacy is also necessary to utilize digital financial services, such as Digital Financial Services (DFS), which facilitate various payment and financial transactions electronically through various digital platforms. However, the use of digital financial services also carries risks, particularly the potential for cybercrime, requiring heightened awareness. Through socialization efforts, understanding digital financial literacy can be enhanced, as demonstrated by the Community Service Implementation Team, which provided education to students of YAPEMRI High School in Depok City on digital financial literacy in its legal aspects. This activity aims to increase students' understanding of financial literacy and various issues in the digital financial domain, such as cybersecurity risks, online fraud, and personal data breaches. Additionally, students were taught the importance of maintaining data integrity, understanding legal rights and obligations in digital transactions, and identifying and addressing potential cybercrimes when using digital financial services.